A comparative study of analgesic effect between ultrasound-guided posterior vis-a-vis lateral transversus abdominis plane block in patients undergoing total abdominal hysterectomy with bilateral salpingo-oophorectomy under spinal anesthesia - Rajib Sikder; Sankar Roy; Arunava Biswas; Dipasri Bhattacharya (Asian Journal of Medical Sciences)
Background: Transversus abdominis plane (TAP) block is used to reduce pain after total abdominal hysterectomy and bilateral salpingo-oophorectomy (TAH+BSO). Two important approaches are ultrasound-guided lateral and posterior approaches. Ultrasound-guided blocks help in the correct localization of the plane and proper deposition of drugs.